Construction of tourism cycle indicator : a signalling tool for tourism market dynamics - Soh, Ann Ni; Puah, Chin Hong; Mohammad Affendy, Bin Arip (Universit`a del Salento, 2019)
The composite leading indicators approach has been popularised in general business and property forecasting extensively, but only rarely in a tourism framework. By utilising the National Bureau of Economic Research (NBER) approach in the construction of a tourism cycle indicator (TCI) for Maldives, a significant signalling attribute regarding international tourists arrivals (TA) to Maldives can be determined. This study spanned approximately two decades of data (2000-2017). Both logarithm forms of TCI and TA with seasonal adjustment are detrended by Hodrick-Prescott (HP) filter. Turning points are detected using Bry-Boschan (BB) dating algorithm. This study explored the possibility of a TCI to capture the information needed for policy planning, risk monitoring and community development. Empirical findings highlighted that the forecasting ability of TCI is vital in reducing crisis burden and should be considered by Maldivians policymakers and tourism industry players.